ANALISIS HUKUM TERHADAP PERCERAIAN SUMPAH LI’AN - Angga Tiara Wardaningtias; Inayatul Anisah (Indonesian Journal of Law and Islamic Law (IJLIL), 2020)
The consequence of divorce by li’an vows is the breakup of the lineage of the child with his father and the end of the marriage forever. Bondowoso Religious Court is one of the Religious Courts that decide divorce by another oath. The judge's consideration in deciding the oath of allegiance by the legal basis in the Compilation of Islamic Law (KHI), namely article 162. However, submitting a child denial application is not following article 102 of the Compilation of Islamic Law. Decision number 0918 / Pdt.G.2019 / PA.Bdw exceeds the time limit allowed to apply for child denial. The Judge of the Religious Court has not yet used Perma No. 03 of 2017 on Guidelines for Judging Women's Matters Facing the Law, as a guideline for judging women in a conference. So that the understanding of gender is still lacking and even do not agree with the concept of gender. What is meant by injustice here is when one type of gender is better in its state, position, and position.